Method for synthesizing high-entropy oxyhydroxide nanosheet through topological transformation

The method of synthesizing high-entropy hydroxyl oxide nanosheets through topological transformation solves the trade-off between activity and stability of existing catalysts, achieving highly efficient OER catalysis, especially exhibiting long-term stability in zinc-air batteries.

CN119284971AActive Publication Date: 2025-01-10UNIV OF SCI & TECH BEIJING +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411177441.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-01-10
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

Existing metal hydroxide and hydroxyl oxide catalysts have difficulty balancing activity and stability in the oxygen evolution reaction (OER), especially iron-based catalysts which have poor stability under high acid and high alkaline conditions, and the uniform synthesis of multi-metal components is difficult to achieve.

Method used

A method for synthesizing high-entropy hydroxyl oxide nanosheets using topological transformation was employed. This method involves combustion synthesis of precursors and structural reconstruction steps, followed by low-temperature solution combustion synthesis and high-energy ultrasonic activation to form limonite-type oxide powder rich in ordered oxygen vacancies. Then, ion exchange reactions were carried out to prepare highly active ultrathin nanosheets.

Benefits of technology

The prepared high-entropy hydroxyl oxide nanosheets exhibited an overpotential of less than 267 mV during the OER process, which significantly improved catalytic stability. The assembled zinc-air battery could operate stably for more than 225 hours at a low charging voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284971A_ABST
    Figure CN119284971A_ABST
Patent Text Reader

Abstract

The invention provides a method for synthesizing a high-entropy oxyhydroxide nanosheet through topological transformation, and belongs to the technical field of inorganic materials, and the method comprises the following steps: 1) component design: carrying out element doping by taking a Ca2Fe2O5 limonite type oxide as a base material; (2) combustion synthesis of a precursor: carrying out in-situ compounding on the raw materials in the step (1) by utilizing a low-temperature solution combustion synthesis method, and combusting the obtained powder to prepare limonite type oxide powder rich in ordered oxygen vacancies; and 3) structure reconstruction: carrying out high-energy ultrasonic activation on the limonite type oxide powder rich in ordered oxygen vacancies obtained in the step 2) to form a high-activity ultrathin structure nanosheet, and then carrying out an ion exchange reaction to obtain the high-entropy oxyhydroxide nanosheet electrocatalyst. Compared with the traditional NiFe and CoFe hydroxide / oxyhydroxide, the nanosheet catalyst also shows higher Fe leaching resistance in the OER process. And the assembled zinc-air battery can stably run for more than 225 hours under low charging voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic materials, and particularly relates to a method for synthesizing high-entropy oxyhydroxide nanosheets through topological transformation. Background Art

[0002] The oxygen evolution reaction (OER) plays a vital role in green energy conversion and storage technologies, such as hydrogen production and water splitting for metal-air batteries, and has attracted widespread attention. It is a multi-electron proton transfer process involving various oxygen intermediates, which requires efficient catalysts. Transition metal hydroxides and oxyhydroxides, especially those based on Fe, Co, and Ni elements, are widely regarded as effective electrocatalysts for OER in alkaline environments. However, current metal hydroxide and oxyhydroxide catalysts have difficulty in balancing activity and stability, especially with regard to iron. Catalysts lacking iron generally exhibit poor intrinsic activity, and stability issues caused by iron leaching are prevalent in iron-containing catalysts when exposed to the high-acid and high-base conditions of OER.

[0003] Studies have shown that multi-metallic and even high-entropy components can induce additional lattice distortions and vacancies, which may enhance the intermediate evolution and charge transfer in OER. However, common synthetic strategies such as co-precipitation and hydrothermal methods have difficulty in achieving uniform multi-metallic components. This is due to the changes in the reaction barriers of different metal cations, as well as the differences in the nucleation and growth rates of their hydroxides. This highlights the necessity of developing a general method for the synthesis of multi-metal oxyhydroxides. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a method for synthesizing high entropy oxyhydroxide nanosheets through topological transformation, wherein the powder preparation process is divided into two steps: combustion synthesis of precursors and structural reconstruction. The obtained product has a high entropy oxyhydroxide nanosheet at 10 mA. cm -2 The catalyst also exhibited a higher resistance to Fe leaching during the OER process than conventional NiFe and CoFe hydroxides / oxyhydroxides. The assembled Zn-air battery was able to operate stably for more than 225 h at a low charge voltage.

[0005] The technical solution provided by the present invention is as follows:

[0006] The present invention provides a method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation, comprising the following steps:

[0007] 1) Composition design: Element doping is carried out with Ca2Fe2O5 limonite-type oxide (A2B2O5) as the matrix material. The doping element at the A site is an alkaline earth metal or a lanthanide metal element, and the doping element at the B site is a transition metal element;

[0008] 2) Combustion synthesis precursor: The raw materials in step 1) are in-situ compounded by the low-temperature solution combustion synthesis method, and the obtained powder is calcined at 800 - 1200 °C for 18 - 36 hours to prepare limonite-type oxide powder rich in ordered oxygen vacancies;

[0009] 3) Structure reconstruction: The limonite-type oxide powder rich in ordered oxygen vacancies obtained in step 2) is activated by high-energy ultrasound to carry out topological transformation and lamellar exfoliation to form highly active ultrathin structure nanosheets, and then an ion exchange reaction is carried out to obtain the high-entropy hydroxy oxide nanosheets.

[0010] Furthermore, the raw materials for element doping in step 1) are metal soluble salts and glycine, and the molar ratio of metal soluble salts to glycine is 2:1. The detailed ratio calculation of metal salts is carried out based on the limonite oxide with the molecular formula A2B2O5. The dosage of various metal salts is calculated according to the ratio of the doping elements at the Ca site, A site, Fe site and B site as x:2 - x:y:2 - y. After doping, the molecular formula of the limonite-type oxide is Ca x A 2-x Fe y B 2-y O5. The value ranges of x and y are 0 < x < 2 and 0 < y < 2 respectively. For example, Ca 1.8 La 0.2 Fe 1.8 Co 0.2 O5.

[0011] Furthermore, the doping element at the A site in step 1) is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), magnesium (Mg), strontium (Sr), barium (Ba).

[0012] Furthermore, the doping element at the B site in step 1) is selected from at least one of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn). Due to the synthesis of perovskite materials, the ionic radii of doping at the A site and B site need to meet certain conditions, and the above elements are selected after screening.

[0013] Furthermore, in step 2), the low-temperature solution combustion synthesis method comprises: preparing a mixed solution containing a metal salt of the element in step 1), performing complexation and evaporation concentration on the mixed solution to form a gel, and then performing a rapid spontaneous combustion reaction at 200-500°C to obtain a powder. The metal salt is a water-soluble salt of the above-mentioned A-position doping element and B-position doping element, such as chloride, nitrate, sulfate, etc.

[0014] Furthermore, the high-energy ultrasonic activation frequency in step 3) is 20-50 KHz, the input power is 500-1000W, and the ultrasonic activation time is 3-5 hours. During the ultrasonic activation process, the Ca element at the A site is unstable and dissolves along the oxygen vacancy channel, causing the structure to be destroyed and collapsed. The original octahedral point-sharing structure is transformed into edge-sharing, and a topological transformation and sheet peeling occur, forming an ultra-thin structured nanosheet with high activity.

[0015] Further, the ion exchange described in step 3) is carried out in a metal salt solution having a solubility less than that of calcium hydroxide, and the metal salt solution for ion exchange is selected from at least one of magnesium (Mg), cerium (Ce), praseodymium (Pr), samarium (Sm), rubidium (Ru), chromium (Cr), manganese (Mn), nickel (Ni), copper (Cu), and zinc (Zn) metal soluble salts. The metal soluble salt is a water-soluble salt, such as chloride, nitrate, sulfate, etc. The concentration of the metal salt solution is 0.01-0.03 mol / L. In this step, due to the difference in solubility, the remaining Ca ions located in the ultra-thin nanosheet layer undergo ion exchange in the weakly acidic metal salt solution to obtain a structurally reconstructed high-entropy hydroxy oxide nanosheet electrocatalyst. The amount of solute in the metal salt solution depends on whether partial or complete unreserved ion exchange is performed. Specifically, according to the calcium content in the nanosheet obtained by ultrasonic activation, the amount of metal salt used to completely or partially replace the calcium element is determined. If the calcium element in the nanosheet is completely replaced, an excess amount of solute is added to the metal salt solution; if the calcium element in the nanosheet is partially replaced, an insufficient amount of solute is added to the metal salt solution.

[0016] The invention also provides high entropy oxyhydroxide nanosheets prepared by the method.

[0017] The present invention also provides the use of the high entropy oxyhydroxide nanosheet as an electrocatalyst in a zinc-air battery.

[0018] This paper proposes a general method for preparing multi-component transition metal oxyhydroxide ultrathin nanosheets from limonite oxide for efficient and durable OER catalysis. First, a calcium-rich limonite oxide precursor with a flexible structure can be quickly synthesized by solution combustion technology and calcination, which is convenient for element adjustment. Subsequently, with high energy input of ultrasound, Ca 2+A large amount of dissolution occurs, and the point-sharing structure of the metal oxygen octahedron is transformed into an edge-sharing structure, resulting in structural collapse and topological transformation to the oxyhydroxide phase. Finally, ion exchange is performed to achieve the synthesis of high-entropy oxyhydroxide ultrathin nanosheets.

[0019] The beneficial effects brought by the present invention include at least:

[0020] 1. Compared with high-entropy hydroxides prepared by traditional processes such as coprecipitation and hydrothermal processes, this method will produce a strong redox reaction, and once the combustion reaction occurs, it can proceed spontaneously. 2. The elements of the synthesized high-entropy hydroxy oxide are evenly distributed without element segregation. Due to the ultra-thin nanosheet structure, the active sites are fully exposed. 3. This method has a certain universality, and the element ratio can be adjusted at will according to needs, so as to prepare electrocatalysts with different catalytic properties. The ultra-thin nanosheets of multi-component hydroxy oxide prepared by the present invention provide an ultra-low overpotential of less than 300 mV, which can effectively reduce energy consumption. Due to the enhanced iron leaching resistance, the catalytic stability is significantly improved. The assembled zinc-air battery can operate stably for more than 225 hours at a low charging voltage. The preparation method provided by the invention provides valuable insights into the synthesis of multi-component hydroxy oxides and highlights the huge potential of multi-component catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 It is the XRD spectrum of the crystal transformation before and after the structural reconstruction in Example 1 of the present invention.

[0023] Figure 2 This is a TEM electron microscope photograph of the CoFeZn hydroxide oxide in Example 1 of the present invention.

[0024] Figure 3 This is the EDS surface scan spectrum of CoFeZn hydroxide oxide in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0026] Example 1

[0027] Ca2CoFeO5 limonite oxide was used as a precursor. Calcium nitrate, cobalt nitrate, iron nitrate and glycine were dissolved in water at a molar ratio of 2.0:1.0:1.0:2.0 to prepare a solution. The mixed solution was complexed and evaporated to form a gel. The gel was heated at 200 °C. The gel volatilized, concentrated and burned to obtain an oxide powder. The oxide powder was then calcined at 1100 °C at a heating rate of 10 °C / min for 24 hours to obtain Ca2CoFeO5 limonite oxide. The prepared limonite powder was subjected to high-energy ultrasonic treatment in 1M KOH solution for 3 hours. The high-energy ultrasonic activation frequency was 20 KHz and the input power was 500 W. The powder was then collected by centrifugal washing. 400 mg of the ultrasonically activated powder was immersed in 40 ml of 0.01MZnCl2 solution for 2 hours of ion exchange to obtain CoFeZn hydroxy oxide. 10 mA was measured cm -2 The lower overpotential is 267 mV, and the assembled zinc-air battery can operate stably for 242 hours.

[0028] Figure 1 The following is an XRD spectrum of the crystal transformation before and after structural reconstruction in Example 1 of the present invention. The lower part is the spectrum before structural reconstruction, indicating that the oxide powder is a limonite crystal with good crystallization; the upper part is the spectrum after structural reconstruction, indicating that the limonite structure collapsed after ultrasonic activation, and the spectrum belonging to hydroxy oxide appeared. The reason for this is that with the high energy input of ultrasound, Ca 2+ Extensive dissolution occurs, and the point-sharing structure of metal oxygen octahedra transforms into an edge-sharing structure, resulting in structural collapse and topological transformation to an oxyhydroxide phase.

[0029] Figure 2 TEM photo of CoFeZn oxyhydroxide in Example 1 of the present invention. It can be seen that the size of the nanosheet is about 100 nm, showing an ultra-thin nanoscale sheet morphology.

[0030] Figure 3 This is the EDS surface scan spectrum of CoFeZn oxyhydroxide in Example 1 of the present invention. Among them, the one in the upper left corner is a dark field image, and the other three are EDS surface scan results of the three elements Co, Fe, and Zn at the corresponding positions. From the EDS surface scan results under high magnification, it can be analyzed that the Co, Fe, and Zn elements are evenly distributed without element segregation, and Zn is evenly doped to replace all the remaining Ca after ultrasonic activation. 2+ .

[0031] Table 1 is the energy spectrum data of CoFeZn oxyhydroxide in Example 1, and it can be seen that the contents of Co, Fe, and Zn in the oxyhydroxide are similar.

[0032] Table 1

[0033]

[0034] Example 2

[0035] Ca2Co 0.6 Fe 0.8 Mn 0.6 O5 limonite-type oxide is used as a precursor, calcium nitrate, cobalt nitrate, iron nitrate, manganese nitrate and glycine are dissolved in water at a molar ratio of 2.0:0.6:0.8:0.5:2.0 to prepare a solution, the mixed solution is complexed and evaporated to form a gel, the gel is heated at 200 ° C, the gel undergoes volatilization, concentration and combustion reactions to obtain oxide powder, and then a high-temperature calcination treatment at 1200 ° C is carried out at a heating rate of 10 ° C / min, and the temperature is kept for 24 hours to obtain Ca2Co 0.6 Fe 0.8 Mn 0.6 O5 limonite oxide. The prepared limonite powder was treated with high-energy ultrasound for 3 hours, with a high-energy ultrasound activation frequency of 20 KHz, an input power of 500 W, and an ultrasound activation time of 3.5 hours. 400 mg of the ultrasonically activated powder was immersed in 40 ml of 0.01 M ZnCl2 solution for 2 hours of ion exchange, and then the powder was collected by centrifugal washing to CoFeMnZn hydroxide. 10 mA was measured cm -2 With a lower overpotential of 290 mV, the assembled zinc-air battery can operate stably for 253 hours.

[0036] Example 3

[0037] Ca2Co 0.4 Fe 0.8 Mn 0.4 Cu 0.4 O5 limonite-type oxide is used as a precursor, calcium nitrate, cobalt nitrate, iron nitrate, manganese nitrate and glycine are dissolved in water at a molar ratio of 2.0:0.4:0.8:0.4:0.4:2.0 to prepare a solution, the mixed solution is complexed and evaporated to form a gel, the gel is heated at 200 ° C, the gel undergoes volatilization, concentration and combustion reactions to obtain oxide powder, and then a high-temperature calcination treatment at 1200 ° C is carried out at a heating rate of 10 ° C / min, and the temperature is kept for 24 hours to obtain Ca2Co 0.4 Fe 0.8 Mn 0.4 Cu 0.4O5 limonite oxide. The prepared limonite powder was subjected to high-energy ultrasonic treatment for 3 hours, with a high-energy ultrasonic activation frequency of 30 KHz and an input power of 600 W, and then the powder was collected by centrifugal washing. 400 mg of the ultrasonically activated powder was immersed in 40 ml of 0.01 M NiCl2 solution and ion exchanged for 2 hours to obtain CoFeMnCuNi hydroxide oxide. 10 mA was measured cm -2 The lower overpotential is 297 mV, and the assembled zinc-air battery can operate stably for 236 hours.

[0038] Example 4

[0039] Ca 1.0 La 1.0 Fe 1.8 Co 0.2 O5 limonite-type oxide is used as a precursor, calcium nitrate, lanthanum nitrate, iron nitrate, cobalt nitrate and glycine are dissolved in water at a molar ratio of 1.0:1.0:1.8:0.2:2.0 to prepare a solution, the mixed solution is complexed and evaporated to form a gel, the gel is heated at 200 ° C, the gel undergoes volatilization, concentration and combustion reactions to obtain oxide powder, and then subjected to high-temperature calcination at 1200 ° C, the heating rate is 10 ° C / min, and the temperature is kept for 24 hours to obtain Ca 1.0 La 1.0 Fe 1.8 Co 0.2 O5 limonite oxide. The prepared limonite powder was subjected to high-energy ultrasonic treatment for 3 hours, with a high-energy ultrasonic activation frequency of 20 KHz and an input power of 500 W, and then the powder was collected by centrifugal washing. 400 mg of the ultrasonically activated powder was immersed in 40 ml of 0.01 M MnCl2 solution and ion exchange was performed for 2 hours to obtain LaCoFeMn hydroxide oxide. 10 mA was measured cm -2 The lower overpotential is 299 mV, and the assembled zinc-air battery can operate stably for 226 hours.

[0040] Comparative Example 1

[0041] Using Ca2Fe2O5 limonite oxide as a precursor, calcium nitrate, ferric nitrate and glycine are dissolved in water at a molar ratio of 1.0:1.0:1.0 to prepare a solution, the mixed solution is complexed and evaporated to form a gel, the gel is heated at 200 ° C, the gel undergoes volatilization, concentration and combustion reactions to obtain an oxide powder, which is then subjected to a high-temperature calcination treatment at 1100 ° C, with a heating rate of 10 ° C / min, and kept warm for 24 hours to obtain Ca2Fe2O5 limonite oxide. The subsequent high-energy ultrasound and ion exchange process is the same as in Example 1 to obtain FeZn hydroxide oxide. 10 mA was measured cm -2 The lower overpotential is 355 mV, and the assembled zinc-air battery can operate stably for 77 hours.

[0042] In Comparative Example 1, compared with Example 1, in step 1), the Ca2Fe2O5 limonite-type oxide AB position doping was not performed, and the product overpotential increased and the battery operating time decreased, indicating that the doping element and the matrix element can interact with each other, reduce the energy barrier in the OER reaction process, and promote the occurrence of the OER reaction process.

[0043] Comparative Example 2

[0044] Ca2CoFeO5 limonite oxide was used as a precursor, and the powder was collected after high-energy ultrasonic activation. No ion exchange was performed. The other steps were the same as in Example 1 to obtain CaCoFe hydroxide oxide. 10 mA was measured. cm -2 With a lower overpotential of 330 mV, the assembled zinc-air battery can operate stably for 91 hours.

[0045] Compared with Example 1, in Comparative Example 2, no ion exchange was performed in step 3), and the product overpotential increased and the battery operating time decreased, indicating that the inert element Ca in the OER reaction process was replaced during the ion exchange process, which was beneficial to promote the OER reaction, reduce the overpotential required for the reaction, and increase the operating time of the zinc-air battery.

[0046] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation, characterized in that: The following steps are involved: 1) Composition design: Ca2Fe2O5 limonite-type oxide is used as the matrix material for element doping, the doping element at the A position is an alkaline earth metal or lanthanide metal element, and the doping element at the B position is a transition metal element; 2) Combustion synthesis precursor: The raw materials of step 1) are in-situ compounded by low-temperature solution combustion synthesis method, and the obtained powder is calcined at 800-1200° C. and kept at this temperature for 18-36 hours to prepare a limonite-type oxide powder rich in ordered oxygen vacancies; 3) Structural reconstruction: The limonite-type oxide powder rich in ordered oxygen vacancies obtained in step 2) is subjected to high-energy ultrasonic activation to form ultrathin structured nanosheets with high activity, followed by an ion exchange reaction to obtain the high-entropy hydroxy oxide nanosheets.

2. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 1, characterized in that: Step 1) The raw materials for element doping are metal soluble salt and glycine, and the molar ratio of the metal soluble salt to glycine is 2:

1.

3. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 2, characterized in that: Step 1) The molecular formula of the limonite-type oxide after doping is Ca x A 2-x Fe y B 2-y O5, the amount of each metal salt is calculated based on the ratio of Ca-doping element, A-doping element, Fe-doping element and B-doping element as x:2-x:y:2-y, where 0 <x<2,0<y<2。 4. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 3, characterized in that: The A-position doping element in step 1) is selected from at least one of lanthanum, cerium, praseodymium, neodymium, samarium, magnesium, strontium and barium; The B-site doping element is selected from at least one of titanium, vanadium, chromium, manganese, cobalt, nickel, copper and zinc.

5. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 4, characterized in that: In step 2), the low-temperature solution combustion synthesis method comprises: preparing a mixed solution containing the metal salt of the element in step 1), complexing and evaporating the mixed solution to form a gel, and then undergoing a rapid spontaneous combustion reaction at 200-500°C to obtain a powder.

6. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 1, characterized in that: The high-energy ultrasonic activation frequency in step 3) is 20-50 KHz, the input power is 500-1000 W, and the ultrasonic activation time is 3-5 hours.

7. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 1, characterized in that: The ion exchange in step 3) is carried out in a metal salt solution having a solubility lower than that of calcium hydroxide.

8. The method for synthesizing high entropy oxyhydroxide nanosheets by topological transformation according to claim 7, characterized in that: The metal salt solution for ion exchange is selected from at least one of soluble metal salts of magnesium, cerium, praseodymium, samarium, rubidium, chromium, manganese, nickel, copper and zinc, and the concentration of the metal salt solution is 0.01-0.03 mol / L.

9. High entropy oxyhydroxide nanosheets prepared by the method of claims 1 to 8.

10. Use of the high entropy oxyhydroxide nanosheets according to claim 9 as an electrocatalyst in a zinc-air battery.

Citation Information

Patent Citations

  • Method for preparing iron-based composite oxide Ca2Fe2O5

    CN102173463A

  • Preparation method of calcium-iron type Ca2Fe2O5 catalyst

    CN107857301A

  • Ionic conductor

    CN116034091A

  • Activation method and application of oxide catalyst for oxygen evolution electro-catalysis

    CN117867561A

  • Material for oxygen evolution (OER) electrode catalyst, and use thereof

    WO2020096022A1